How real are Macroeconomic Parameters of Romania during 1989-2009 - Angelica BĂCESCU-CĂRBUNARU (Revista de Management Comparat International)
The main idea of this article is that GDP of Romania related to the last 12 years is extremely high and creates the illusion that in a short period of time it could become a developed country from economic viewpoint. Based of the analysis of macroeconomic indicators from official statistical publications, the necessary arguments are brought to demonstrate how real macroeconomic parameters of Romania are during 1989-2009.